Pembelajaran REACT (Relating, Experiencing, Applying, Cooperating, and Transferring) di Era Pendidikan Abad 21 - Junaidah, Emy; Nurdin, Nurdin; Solihin, Rahmat (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to determine the application of REACT learning strategies and the impact arising from implementing these strategies. This research method is descriptive qualitative which describes the results of research conducted in the field by interviewing, observing, and documenting at three educational institutions namely SDN 006 Muara Jawa, SDN 008 Muara Jawa, and SDN 014 Muara Jawa. Based on the results of the study it can be seen that the steps for implementing the strategy at SD Pesisir Muara Jawa which REACT are reflected in the acronym, are: (1) connecting/connecting (relating), (2) experiencing (experiencing), (3) implementing (applying), (4) working together (cooperating), and (5) transferring (transferring). The application of the REACT learning strategy has positive and negative impacts on the learning process, one of which is that students are more active in learning and can make teachers prepare a lot of preparations in the learning process. The results of implementing this strategy are very effective in improving student learning outcomes, besides being effective it is also fun for students.